Sosialisasi Penguatan Ideologi Pancasila pada Mahasiswa Anggota Racana Pramuka di Perguruan Tinggi - Andi Sri Wahyuni Mumang; Andika Marsuki; Nursalim Nursalim (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2025)
This community service activity aims to strengthen the understanding and practice of Pancasila values as the state ideology for scout group members in the university environment. This is motivated by the phenomenon of low ideological awareness among young people, especially students, which can become a serious challenge in maintaining the unity and identity of the nation. The activity is carried out as a means to strengthen student character so that they have great potential to instill national values. The activity is implemented through a participatory approach, including lectures and interactive discussions. The results of the activity show an increase in students' knowledge and awareness of Pancasila values, reflected in their commitment to continue internalizing Pancasila values both within and outside the campus environment. This activity is expected to serve as an initial step in shaping a young generation with Pancasila character, integrity, and a strong sense of nationalism.